Biochemical Features and Physiological Roles of hNP22 in the Central Nervous System - Wu, Ji; Wang, Yun-Yi; Yang, Xi-Wen; Zhang, Xiao-Tian; Tang, Jia-Yi (Frontiers in Cell and Developmental Biology, 2021)
hNP22, as a novel neuron-specific protein interact with both actin filaments and microtubules, featuring motifs previously described in cytoskeleton-associating and signaling proteins. hNP22 was found to be highly homologous with smooth muscle cell cytoskeleton-associated proteins, human SM22α and rat acidic calponin. In recent years, functions of hNP22 such as promotion of neural differentiation and enhancement of neural plasticity, as well as links with diseases such as schizophrenia and alcohol-related brain damage (ARBD) have been described. With the potential roles of hNP22 in neuronal processes and its potential implications in diseases, hNP22 emerges as an interesting target for further studies. In this paper, we review the structure of the TAGLN3 gene that codes for hNP22 protein, the possible modifications, functions and clinical implications of hNP22 protein, as well as the directions for future studies. Given its possible physiological roles in the central nervous system, the involvement of hNP22 in neurological disorders, such as schizophrenia and alcohol-related brain damage, has been purposed.